A influência da inovação no desempenho das firmas no Brasil - Shimizu, Ullisses Kazumi (2013)
The innovation has been considered the engine of the major developments that capitalism has reached, and under this umbrella, this study aims to evaluate the causal relationship between innovation of Brazilian firms and their performance.The study of this subject is justified by the importance of the topic in academia, nationally and internationally, and also by the need to do a study that took into account both Micro, Small and Medium Enterprises (MSMEs), as large companies, in addition to analyzing the new service sector recently (2005) included in Technological Innovation Research (PINTEC).We crossed the CNPJs (national registry of legal companies) at PINTEC with those contained in the Annual Industrial Survey - PIA and the Annual Services Survey - PAS, and create variables to measure seven constructs: Innovative Activity, R&D Internal Activity, Innovation Cooperation, Government Support, Patent and other Protection Machanisms, Organizational and Marketing Innovation, and Performance.The three surveys are periodically conducted by the Brazilian Institute of Geography and Statistics (IBGE). We used exploratory factor analysis in order to aggregate related variables and structural equation modeling, to create models that can better explain the relationship between innovation and performance. We note the existence of a relationship between innovation and the result of the innovation process latent variable measured by the "impact of innovations", formed by iivli (share of sales of new products related to sales of the company) and iiexp (share of exports of new products in relation to sales of the company), in the converged models, the inpact was approximately 40%.However, the relationship between innovation and performance (measured by profitability and margin) was not supported.